Avaliação de diferentes protocolos para edição gênica pela metodologia CRISPR/Cas9 em Leishmania amazonensis. - Carlos Rodolpho Ferreira Brasil (2020)
The CRISPR/Cas9 system has been considered as a revolutionary tool to promote gene edition in a wide array of organisms. The knockouts and knock-ins generated by CRISPR/Cas9 allow better understanding of cellular, metabolic or structural impacts caused by addition or removal of some component, which may result in advances related to vaccine development, diagnostic or therapeutic interventions. CRISPR/Cas9 has already been applied in different studies for different Leishmania species, but not to Leishmania amazonensis, one of the most important etiologic agents of tegumentary leishmaniasis. In the present work, we tested different CRISPR/Cas9 protocols to introduce knockout on L. amazonensis Miltefosine Transporter (MT) as a proof of concept. The expression of Streptococcus pyogenes Cas9 (SpCas9) was obtained by transfection with two plasmids: pLDCN, which is an epissomal vector and pRM006, which contains homology arms with beta-tubulin UTR sequences, promoting homologous recombination, and integration to the genome. A Donor sequence containing three stop codons in tandem as well as a restriction site for HindIII and 30bp homology arms was also given to the transfected cells to guide the double strand break repair though homology. Alternatively, we expressed Staphylococcus aureus Cas9 (SaCas9) on Escherichia coli and assorted its activity in vitro. Promastigotes were transfected with a ribonucleoprotein complex of the recombinant SaCas9 and a SgRNA. MT edition was confirmed on parasites transfected with pLDCN and an in vitro transcribed SgRNA, designed to this species, despite the limitations associated with the current L. amazonensis genome sequence available, and as well as with recombinant SaCas9. Parasites previously transfected with pRM006 lost their resistance to higromicine and weren’t edited. The cell line generated using recombinant SaCas9 showed to be approximately 6 times more resistant to miltefosine than its wild type counterpart. We evaluated the infectivity of this mutant cell line to bone marrow derivated macrophages. However, no significant difference was observed when comparing it to wild types. Together, our results showed the possibility of genome editing in L. amazonensis with different protocols of CRISPR/Cas9, which may still be optimized. The miltefosine resistant parasites may now be better characterized regarding the phenotypic changes related to the MT gene edition.